MODALITAS Kí–NNEN DALAM KALIMAT BAHASA JERMAN - Triyono, Sulis (Diksi, 2015)
This article is an introduction to the basic concept of using the modality of k nnen ’can’ in German sentences. The k nnen unit of modality functions to reveal the speaker’s attitude and has the status of a verb modifier. Modality is divided in function by some linguists into different areas like epistemic modality, modalitymarking adverb, and deciderative and optative mode devices. On the basis of the results of a study conducted, it could be concluded that the modality unit of kí¶nnen ’can’ in a sentence in German has the characteristics as follows: (1) it is merely an attributive element in a verb phrase rather than a core one so that if deleted the sentence remains grammatical, (2) its relation to any other element is loose in nature, and (3) its position is so firm that it cannot be permutated with any other element in a sentence. In addition, in sentences the kí¶nnen modality varies in meaning according to sentence context. The meaning expressed by the kí¶nnen modality can be of possibility, ability, or permission. Keywords: the kí¶nnen modality